Engagement strategies in the context of the Itabira mine closure: impacts and stakeholder participation - Barreto, Rodrigo Silva (2024)
Purpose: This article aims to propose and apply a set of analytical categories for evaluating engagement in mine closure processes. Design/methodology/approach: The qualitative research adopts a case study strategy considering the singularity of the phenomenon studied. The mine project analyzed is the country's first large-scale closure, scheduled for 2041, with the potential to influence future processes. Data collection involved observation, documentary analysis, and interviews. Sixteen interviews were conducted with representatives from the public power, community, organizations, and the company. The research strategy chosen was content analysis using the analytical categories raised in the literature review and triangulation of data collection sources. Findings: The results highlight the importance of the mining company's active role in constructing the city's post-mining future, collaborating to reconvert socio-economic dynamics, and fostering a trusting relationship with the community. However, the company remains distant from the debate. Interviews revealed a paternalistic relationship between the mining company that guides engagement in a predominantly unilateral flow, with communication directed to meet its interests. Originality/value: This research fills a gap in the existing literature by focusing on engagement in a vulnerable context. It contributes to the theoretical advancement of the main characteristics of engagement in mine closure processes and for dialogue practices with communities to favor sustainable territory development in the post-mining period.